1999
DOI: 10.1055/s-2007-994931
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Resistance and Thrombosis: Molecular Mechanisms of Hypercoagulable State Due to FVR506Q Mutation

Abstract: Inherited resistance to activated protein C (APC) is the most common genetic risk factor of venous thrombosis. It is caused by a single point mutation in the factor (F)V gene which predicts replacement of Arg506 with a Gln (FVR506Q, FV: Q506 or FV Leiden). This mutation affects the function of the protein C system, a physiologically important natural anticoagulant pathway. APC inhibits coagulation by cleaving a limited number of peptide bonds in both intact and activated forms of factor V (FV/FVa) and factor V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 143 publications
1
41
0
4
Order By: Relevance
“…11,12 In 90% of patients, it is caused by a point mutation in FV that results in the replacement of Arg506 with Gln (FV Leiden). 12,13 This inhibits the efficiency by which APC degrades FVa; in addition, it impairs the APC cofactor function of FV in the degradation of FVIIIa because 506-cleavage is needed for the generation of full anticoagulant FV function. 10,14 These dual functions of the FV Leiden mutation result in the generation of a hypercoagulable state, which constitutes a lifelong risk factor for thrombosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In 90% of patients, it is caused by a point mutation in FV that results in the replacement of Arg506 with Gln (FV Leiden). 12,13 This inhibits the efficiency by which APC degrades FVa; in addition, it impairs the APC cofactor function of FV in the degradation of FVIIIa because 506-cleavage is needed for the generation of full anticoagulant FV function. 10,14 These dual functions of the FV Leiden mutation result in the generation of a hypercoagulable state, which constitutes a lifelong risk factor for thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…10,14 These dual functions of the FV Leiden mutation result in the generation of a hypercoagulable state, which constitutes a lifelong risk factor for thrombosis. 12 In 1998, 2 new mutations in FV, FV Hong Kong and FV Cambridge, were reported among patients with thrombosis. 15,16 Both mutations result in the replacement of Arg306, in FV Hong Kong with a Gly and in FV Cambridge with a Thr.…”
Section: Introductionmentioning
confidence: 99%
“…APCr is in 90% caused by V Leiden factor -a genetic defect affecting approximately 5% of the general population [17]. There is also APCr associated with the use of contraceptives and pregnancy (elevated levels of factor VIII, fibrinogen and von Willebrand factor in a pregnant woman being nongenetic causes of APCr) [18].…”
Section: Activated Protein C Resistance (Apcr) In Cord Bloodmentioning
confidence: 99%
“…More recently it has been reported that the prevalence of FVL-mutation in European populations is approximately 3% to 7% with rare occurrence in black and Asian populations [8].…”
Section: Introductionmentioning
confidence: 99%